Global Economic Prospects, June 2015 : The Global Economy in Transition - World Bank Group (Washington, DC: World Bank, 2015)
Global growth is expected to be 2.8 percent in 2015, but is expected to pick up to 3.2 percent in 2016–17. Growth in developing countries and some high-income countries is set to disappoint again this year. The prospect of rising borrowing costs will compound the challenges many developing countries are facing as they adapt to an era of low commodity prices. Risks to this outlook remain tilted to the downside.